2020
DOI: 10.1002/cam4.3189
|View full text |Cite
|
Sign up to set email alerts
|

The clinical application value of mixed‐reality‐assisted surgical navigation for laparoscopic nephrectomy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…There were no significant differences in other indexes (such as hospital stay, preoperative or postoperative serum creatinine (Scr), and postoperative complications) among the three groups (all P>0.05; Table 5). As a new generation of holographic visualization technology, MR can read image information intuitively, stereoscopically, and comprehensively in the most natural way, which helps surgeons shorten the learning cycle before surgery and quickly locate renal tumors during surgery (3). This study shows that MR can effectively increase successful NSS cases, shorten OT, and decrease WIT and EBL compared with traditional CT imaging.…”
Section: Perioperative Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…There were no significant differences in other indexes (such as hospital stay, preoperative or postoperative serum creatinine (Scr), and postoperative complications) among the three groups (all P>0.05; Table 5). As a new generation of holographic visualization technology, MR can read image information intuitively, stereoscopically, and comprehensively in the most natural way, which helps surgeons shorten the learning cycle before surgery and quickly locate renal tumors during surgery (3). This study shows that MR can effectively increase successful NSS cases, shorten OT, and decrease WIT and EBL compared with traditional CT imaging.…”
Section: Perioperative Resultsmentioning
confidence: 74%
“…In our previous study, Li et al demonstrated that the number of conversions from laparoscopic partial nephrectomy (LPN) to laparoscopic radical nephrectomy (LRN) were 2/50 (4%) and 4/50 (8%) for the MR group and the non-MR group, respectively (3). However, in the present study, we found that the number of conversions from LPN to LRN were 15/50 (30%), 13/50 (26%), and 21/50 (42%) for Group A, Group B, and Group C, respectively.…”
Section: Perioperative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could facilitate visualization and analysis of the patient's preoperative imaging studies for a better and safer approach to surgery. MR devices, in combination with new emerging medical imaging techniques, have been successfully applied as a planning tool in different surgical disciplines such as urology [43], thoracic surgery [44], neurosurgery, colorectal surgery, and bariatric surgery [45], among others.…”
Section: Surgical Assistancementioning
confidence: 99%
“…MR has been proven to be a practical tool for intraoperative surgical guidance in the operating room[ 11 ]. Previous studies have shown that MR has been gradually applied to neurosurgery, orthopedics, and urology, yielding improvements in perioperative outcomes for patients[ 12 - 14 ]. In hepatectomy for patients with HCC, MR also exhibit great potential in preoperative planning and intraoperative navigation, which makes hepatectomy more accurate and personalized[ 15 ].…”
Section: Introductionmentioning
confidence: 99%